Beyond the grey tsunami: a cross-sectional population-based study of multimorbidity in Ontario - Ryan, Bridget L. (Can J Public Health, 2018)
OBJECTIVES: To determine volumes and rates of multimorbidity in Ontario by age group, sex, material deprivation, and geography. METHODS: A cross-sectional population-based study was completed using linked provincial health administrative databases. Ontario residents were classified as having multimorbidity (3+ chronic conditions) or not, based on the presence of 17 chronic conditions. The volumes (number of residents) of multimorbidity were determined by age categories in addition to crude and age-sex standardized rates. RESULTS: Among the 2013 Ontario population, 15.2% had multimorbidity. Multimorbidity rates increased across successively older age groups with lowest rates observed in youngest (0–17 years, 0.2%) and highest rates in the oldest (80+ years, 73.5%). The rate of multimorbidity increased gradually from ages 0 to 44 years, with a substantial and graded increase in the rates as the population aged. The top five chronic conditions, of the 17 examined, among those with multimorbidity were mood disorders, hypertensive disorders, asthma, arthritis, and diabetes. CONCLUSION: Much of the common rhetoric around multimorbidity concerns the aging ‘grey tsunami’. This study demonstrated that the volume of multimorbidity is derived from adults beginning as young as age 35 years old. A focus only on the old underestimates the absolute burden of multimorbidity on the health care system. It can mask the association of material deprivation and geography with multimorbidity which can turn our attention away from two critical issues: (1) potential inequality in health and health care in Ontario and (2) preventing younger and middle-aged people from moving into the multimorbidity category. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.17269/s41997-018-0103-0) contains supplementary material, which is available to authorized users.